Estudo da identificação humana por meio da imaginologia dos seios frontais. - Almeida, Manuella Santos Carneiro (2012)
The aim of this study was to verify the applicability of parameters for human identification using the frontal sinuses, used by Tatlisumak et al. (2007), using axial and coronal reconstructions of CBCT and extraoral radiographs. From 58 dry disjointed skulls existing in the Management of Legal Medicine of Paraiba (PB-GEMOL) and University Center of Joao Pessoa, UNIPÊ, 26 skulls were selected. The acquisition of anteroposterior radiographs of the skull and lateral view were obtained through X-ray machine pan Rotograph Plus ® (Dabi Atlante Ltda., Ribeirão Preto, São Paulo, Brazil) and the CT at New iCAT device Generation ® (Imaging Sciences International, Pennsylvania, USA), adopting a specific methodology in order to standardize the tests to obtain and ensure the reproducibility of the study. The images were evaluated by two examiners calibrated in darkened environment and in two different times, with a minimum interval of one week. Assessments of axial and coronal reconstructions were performed with the aid of a 23 "program and iCat Vision (Imaging Sciences International, Pennsylvania, USA). For evaluation of extraoral radiographs were traced on paper made using ultrafan of 600 lux light box with mask and measurements with the aid of a high precision digital caliper Mitutoyo series 167 (Mitutoyo, Suzano, Brazil). Categorical variables were discrete and analyzed using the kappa test and continuous variables by Correlation Coefficient of Concordance Lin. Methods of analysis by cone beam CT and radiographic were mostly consistent, with only a few variables with unsatisfactory results (capd, and dpele dpontalt). For categorical variables and discrete intra-and inter-was great-perfect for both methods, as continuous variables showed moderate to excellent results. It is concluded that: the methodology proposed in this paper, using the parameters of the job Tatlisumak et al. (2007), are applicable and reliable in extraoral radiographs (X-rays AP and lateral radiographs of the skull face) and axial and coronal reconstructions of CBCT for human identification by frontal sinus, intra-and inter the parameters used by Tatlisumak et al. (2007) with CBCT imaging modality varies from substantial to excellent, and moderate to excellent radiographic images, there is a greater power of reproducibility and accuracy of the proposed method using the axial and coronal reconstructions of CBCT taking extraoral radiographs also reliability , the least consistent variable in the analysis by the images of CBCT is a measure capd (poor agreement), while the radiographic images and are dpele dpontalt (bad matches). This result indicates that these parameters are more susceptible to errors by evaluators, since it needs to use multiple points of reference for their measurements.